Anti-inflammatory activity of cannabinoid receptor 2 ligands in primary hPDL fibroblasts. (March 2018) - Abidi, Ammaar H.; Presley, Chaela S.; Dabbous, Mustafa; Tipton, David A.; Mustafa, Suni M.; Moore, Bob M.
Highlights: Characterization of IL-6 and MCP-1 expression in primary human PDL fibroblasts. IL-6 and MCP-1 response in the presence and absence of stimuli. CB2 ligands downregulate IL-6 and MCP-1 on stimulated hPDL fibroblasts. CB2 agonist and inverse agonist both exert anti-inflammatory activity. Inverse agonist provides better anti-inflammatory activity. Abstract: Objectives: Approximately 65 million adults in the US have periodontitis, causing tooth loss and decreased quality of life. Cannabinoids modulate immune responses, and endocannabinoids are prevalent during oral cavity inflammation. Targets for intervention in periodontal inflammation are cannabinoid type 1 and 2 receptors (CB1R, CB2R), particularly CB2R because its levels increase during inflammation. We previously demonstrated that SMM-189 (CB2R inverse agonist) decreased pro-inflammatory cytokine production in primary microglial cells. The hypothesis of this study was that cannabinoids anandamide (AEA), HU-308 (CB2R selective agonist), and SMM-189 decrease pro-inflammatory IL-6 and MCP-1 production by primary human periodontal ligament fibroblasts (hPDLFs) stimulated with P. gingivalis LPS, TNF-α, or IL-1β. Design: Cytotoxic effects of cannabinoid compounds (10 −4 –10 −6.5 M), LPS (1–1000 ng/ml), TNFα (10 ng/ml) and IL-1β (1 ng/ml) were assessed by measuring effects on cellular dehydrogenase activity. IL-6 and MCP-1 production were measured using Mesoscale Discovery (MSD) Human Pro-Inflammatory IL-6 and MSD Human Chemokine MCP-1 kits and analyzed using MSD Sector 2400 machine. Results: EC50 values for AEA, SMM-189, and HU-308 were 16 μM, 13 μM, and 7.3 μM respectively. LPS (1 μg/ml), TNF-α (10 ng/ml), and IL-1β (1 ng/ml) increased IL-6 and MCP-1 production, which were inhibited by AEA, SMM-189, and HU-308. AEA alone significantly increased IL-6, but not MCP-1 levels, but the other cannabinoids alone had no effect. Conclusion: The effective inhibition of LPS, TNF-α, IL-1β stimulated IL-6 and MCP-1 production by CB2R ligands in hPDLFs suggests that targeting the endocannabinoid system may lead to development of novel drugs for periodontal therapy, aiding strategies to improve oral health.